1973
DOI: 10.1002/chin.197351236
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: DARSTELLUNG VON INDANOL‐(1) UNTER VERWENDUNG VON ANIONITEN

Abstract: Das Indanol (II) wird nach einer neuen Methode aus dem Chlorindan (I) in großer Reinheit erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the course of synthetic work related to 1-benzyl-3(2H)-isoquinolinone it appeared that four prototropic isomers were possible [197] demonstrating the complexity of the problem. The study of the UV spectra of some 3(2H)-isoquinolinones substituted in position 1 with aryl and aralkyl groups in different solvents has been carried out [198]. It has been found that, for example, the 1-β-naphtyl derivative exists exclusively as the lactim tautomer in diethyl ether, carbon tetrachloride and sulfuric acid.…”
Section: -(2h)-isoquinolonesmentioning
confidence: 99%
“…In the course of synthetic work related to 1-benzyl-3(2H)-isoquinolinone it appeared that four prototropic isomers were possible [197] demonstrating the complexity of the problem. The study of the UV spectra of some 3(2H)-isoquinolinones substituted in position 1 with aryl and aralkyl groups in different solvents has been carried out [198]. It has been found that, for example, the 1-β-naphtyl derivative exists exclusively as the lactim tautomer in diethyl ether, carbon tetrachloride and sulfuric acid.…”
Section: -(2h)-isoquinolonesmentioning
confidence: 99%